PENENTUAN LOKASI USAHA BERDASARKAN ARAH MATA ANGIN (Studi fenomenologi Pada Pemborong Padi Di Kecamatan Kesamben) - Endah Masrunik; Arif Arif Wahyudi; Redy Khoirianto; Moh. Zaki Kurniawan (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2021)
This study aims to reveal the strategies of rice wholesalers in determining the right business location according to the cardinal directions to meet consumer needs. Choosing the right location will have an impact on the development of the business. The method uses qualitative method and phenomenological approach, where the researcher explores the high and deep meaning of events or phenomena applied by the contractors in choosing a business location. The result proves the contractors choose the location based on the belief in the wind direction which is adjusted to the Java market day which is difficult to accept logically. Furthermore the choice of business location is based on magical beliefs. The contractor believes that the wind direction that is adjusted to certain days and markets is special and will generate profits used for business activities.